(untitled) (KULT_online, 2021)
According to Possible Worlds Theory and Contemporary Narratology (2019), possible worlds theory was introduced to literary studies when the textualist schools of thought dominated the field. Literary interpretation had come to a dead-end: if everything was language, literary meaning could be interpreted only as a play of language. The edited volume explains how viewing fiction as world-building instead of a language game made it again “possible to say that literary works were about something” (p. 316). The book’s main focus is on what the theory offers to contemporary narratology and developing it further.